Rescue stitch: A minimal access surgeon's lifeboat in life-threatening intraoperative bleeding - Abhishek Singh; Arvind Ganpule (Journal of Minimal Access Surgery, 2019)
Bleeding in a minimal access surgery can be very intimidating for a laparoscopic surgeon. Open conversion becomes an imminent option in these situations. Although open conversion is not a surgical defeat, in certain situations, bleeding can be salvaged using a ‘rescue stitch.’ We, herein, describe rescue stitch along with a rescue tray and its application during intraoperative bleeding in minimal access surgery.